Public willingness to pay and participate in domestic waste management in rural areas of China - Han, Zhiyong; Zeng, Dan; Li, Qibin; Cheng, Cheng; Shi, Guozhong; Mou, Zishen (Resources, conservation and recycling, 2019)
•There was a good basis and extensive support for waste management in countryside.•Demonstration and necessity awareness significantly influence public willingness.•Gender and income play the most important role on public willingness to pay.•Education, age, perception and propaganda could affect public willingness.•Service fee, delivery distance and expected wage need be considered. Broad and sustainable public willingness to pay (WTP) and willingness to participate (WTPP) are the basis of successful domestic waste management. Using questionnaires and statistical methods, we investigated the public WTP (73.72%), the public WTPP including willingness to use collection facilities (90.61%), to sort waste (78.70%), to deliver waste (93.28%) and to dispose waste (69.28%), the public willingness to work as a cleaner (62.50%), and their influential socioeconomic factors in rural areas of China, in order to provide more effective and practical policies for the waste management. Results indicated that men and wealthy subjects had greater WTP than women and poor subjects. Demonstration projects and public awareness of waste treatment necessity had significantly positive effects on WTP and WTPP. Villagers who received propaganda were more WTP and WTPP. Perception of environmental pollution could significantly enhance WTP without considering other factors. The older subjects had weaker WTPP compared with the youngest subjects based on single factor logistic regression. Education had a significant positive effect on and high correlation with WTP and WTPP, respectively. Public WTP and willingness to deliver waste decreased exponentially with increases in service fee and delivery distance, respectively. Public willingness to work as a cleaner exhibited logarithmic growth as expected wages increased. In the future, it will be necessary to take effective measures for rural waste management, such as providing demonstration programs, enhancing public awareness of waste treatment necessity, considering influences of service fees, delivery distance and expected wages, and developing sustainable rural economy to increase residents’ incomes.